Thirty years of geoethic conflicts between natural groundwater vulnerability and land use in a southeastern Brazilian municipality - Guerrero, João; Gomes, Alberto; Mataveli, Guilherme; Lorandi, Reinaldo; Teixeira, José; di Lollo, José Augusto [UNESP]; Moschini, Luiz Eduardo (Springer Nature, 2023)
Geoethics is the research and reflection about values, behaviors, and best practices to adopt in areas where human activities interact with the earth system. Considering that groundwater is one of the most vital natural resources for human survival and that the enormous increase in human pressures on ecosystems poses an imminent threat to its quality, it may be stated that there is a geoethical issue on a worldwide scale. In this context, the present study aimed to analyse the geoethical conflicts between the increase in human activities and the natural vulnerability of aquifers over the past 3 decades in a Brazilian municipality located in the Guarani Aquifer System, one of the world's largest freshwater reservoirs. For this purpose, we utilized geoenvironmental mapping techniques, treated and handled hydrogeological data (geology, soils, depth) from the GODS vulnerability model, and cross-referenced this information with 30 years of local land use data. The results indicated a considerable rise in geoethical conflicts in the region, with high-conflict zones increasing by 800% between 1989 and 2019, primarily as a result of the expansion of sugarcane monocultures and forests over natural environments. This evolution demonstrates that the process of changing land use has occurred without taking into account the potential and limitations of the local environment, endangering the quality and accessibility of drinking water.
Keywords: Environmental planning; Geoenvironmental cartography; Geoethic conflicts; GIS; Groundwater